Effects of Intercropping Aromatic Plants on the Soil Microbiota in Tobacco Field (Bangladesh Journal of Botany, 2023)
By utilising high-throughput sequencing technology, we systematically analysed microbial flora changes in tobacco fields intercropping various Lamiaceae plants that are cultivated mainly for extracting the aromatic compounds. The results showed that the number of soil microorganisms in the rhizosphere changed during the resettling, flourishing, and harvesting periods. Among these periods, the number of actinomycetes in the flourishing period increased, which played a role in enhancing the disease resistance of tobacco plants to a certain extent. The soil microbial diversity analyses revealed that the amount, species and Alpha diversity index of rhizosphere soil microbes were the highest at the resettling and flourishing stages. Bacterial floras belonging toActinobacteria, Firmicutes, Proteobacteria and Nitrospiraewere the dominant ones, playing a certain role in the soil nitrogen cycle and supply. For both bacteria or and fungi, the difference between communities of the soils with the intercropping pattern was greater than that of the control.Bangladesh J. Bot. 51(4): 829-838, 2022 (December) Special